Community-based models of care for adolescent and adult depression, suicidal behavior, anxiety, trauma, and substance use in Africa: a scoping review - Raeber, Fabian; Haldemann, Maria-Inés; Ray, Somidha; Huber, Jacqueline; Firima, Emmanuel; Fernandez, Lucia Gonzalez; Amstutz, Alain; Gerber, Felix; Labhardt, Niklaus D.; Belus, Jennifer M. (Frontiers in Psychology, 2024)
Background Community-based care (CBC), where care is delivered outside of the traditional health facility setting, has been proposed to narrow the mental health (MH) and substance use (SU) treatment gap in Africa. Objective This scoping review aims to comprehensively summarize CBC models addressing adolescent and adult MH (depression, anxiety, trauma, suicidal behavior) and (non-tobacco) SU problems in Africa. Methods We searched PsycINFO, Embase, Scopus, CINAHL, and Medline Ovid. Studies and protocols were included if they reported on CBC intervention’s effects on MH or SU symptoms/ diagnoses, acceptability, feasibility, or patient engagement in care, regardless of whether the intervention itself was designed specifically for MH or SU. Results Among 11,477 screened publications, 217 were eligible. Of the unique intervention studies (n = 206), CBC models were classified into the following approaches (non-mutually exclusive): psychotherapeutic (n = 144), social (n = 81), lifestyle/physical health (n = 55), economic (n = 26), and psychopharmacological (n = 2). While quantitative results suggest possible efficacy of CBC models, description of CBC location was often poor. Fewer interventions addressed suicidal behavior (n = 12), the needs of adolescents (n = 49), or used traditional healers or religious figures as providers (n = 3). Conclusion Many CBC models have been tested on MH and SU in Africa and should be critically appraised and meta-analyzed in subsequent reviews, where possible.